The Nurturance of a Scientist - Kerur, Vandana (THE PRIMARY TEACHER, 2016)
This paper elaborates the emotional journey of a child with reference to the experiences of famous scientist Thomas Alva Edison during his growing-up years. The role of women — in Edison’s case, his mother in early childhood years — have been, particularly, emphasised. This paper highlights the way family plays a crucial role in the holistic development of a child, moving beyond the limitations of social acceptance. The confidence is transferred to the child before one gets acquainted with the nuances of the outside world. Three examples have been illustrated in the paper to delve into details for understanding the fragile nature of the child.